Participação política: uma visão integrada a partir do Modelo do Voluntarismo Cívico e do modelo dos efeitos da legitimidade sobre a participação política - Isis Arantes Maciel de Souza (2013)
This study investigated the phenomenon of political participation. We seek to capture and relate the factors that were explaining the phenomenon in question. To achieve our goal, we combined two analytical models The Model Civic Voluntarism and the model of the effects of legitimacy on political participation - our argument is that both models provide a more explanatory view. Through multivariate analysis we sought to answer four questions: Who are the people that participate in politics? How do the attitudes towards the political regime and its institutions impact political participation and define the channels where it happens? Why do individuals participate? Answering these four questions was the goal of this work. The database used to answer the questions posed by this study was Barômetro das Américas, conducted in 2010.